Produksi Metil Ester Menggunakan Nanokatalis Heterogen - Rif’ah Amalia; Joke Pratilastiarso; Eka Siti Nur Laili (Journal of Research and Technology, 2021)
Fatty acid methyl ester, is one of the alternative fuels for biofuels obtained from animal and vegetable fats through esterification and transesterification processes. In this research, used palm oil as raw material was used using heterogeneous catalysts derived from chicken egg shells. The first used palm oil is filtered to remove impurities that are still present in the oil, then pre-treatment is carried out by testing the acid number, free fatty acid, density and viscosity measurements. Followed by the manufacture of nano catalysts from chicken egg shells by calcination. The results of calcination of the catalyst were carried out by XRD analysis to determine the crystal structure and crystallinity of the resulting product. The process of making methyl esters is carried out by esterification and transesterification processes using heterogeneous catalysts. The results obtained that the best calcination temperature for a 20-gram catalyst was 9000C with a pH value of 14. The longer the reaction temperature in the transesterification process, the yield value of the methyl ester produced increased, where the highest yield value was obtained at a temperature of 600C. The longer the reaction time, the yield value produced will increase, where the highest yield is obtained at a reaction time of 25 minutes, which is 87.98%. From testing the physical and chemical properties of methyl ester, the results of the analysis of methyl ester products are within the limits of SNI Biodiesel.